Circular Economy: A Technological Innovation Strategy for Sustainability in Air Transport - Castillo Malagón, Romina; Cruz Reyes, María Angélica; Romero Saldaña, Ruth Selene (Mercados y Negocios, 2024)
This work aims to identify innovations, technological advances, and best practices to migrate towards a circular economy in air transport. The relevance of the research lies in the contribution to the generation of circular economy knowledge in the field of administration with application in the aeronautical industry. By analyzing literature and best practices, the circular economy could be a viable solution to reduce the use of natural resources in aircraft manufacturing and airport operations. Among the main findings are innovations and technological developments in new materials, fuels, building methods, and best practices implemented at airports to obtain energy and generate less waste. It has also been identified that applying circular economy principles in this mode of transport would contribute to sustainability efforts and increase the competitiveness of organizations in the sector.